تطوير الحوكمة الشرعية في المصارف الإسلامية في أفغانستان: دراسة تحليلية في ضوء التجربة الماليزية: Developing Shariah Governance in Islamic Banks in Afghanistan: An Analytical Study in Light of the Malaysian Experience - Anwarul Haq, Amiri; Ghalia, Bouhedda; Sitiris, Miszairi; Mohammad Tahir, Sarfaraz (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يقدم هذا البحث دراسة تحليلية متعمقة للحوكمة الشرعية في النظام المصرفي الإسلامي، مع مقارنة بين التجربة الأفغانية والتجربة الماليزية الرائدة. يرتكز البحث على مراجعة الأدبيات وتحليل القوانين واللوائح ذات الصلة، بالإضافة إلى مقابلات مع خبراء القطاع، لاستكشاف كيفية تطبيق الحوكمة الشرعية في تحقيق الامتثال للشريعة الإسلامية وتعزيز الاستقرار المالي. أظهرت النتائج تفوق التجربة الماليزية بفضل الإطار القانوني الشامل، واستقلالية المجالس الشرعية، واعتماد معايير تشغيلية متقدمة، مثل قانون الخدمات المالية الإسلامية لعام 2013 ومعيار الحوكمة الشرعية لعام 2019. في المقابل، يعاني النظام الأفغاني من غياب قانون مستقل للمصرفية الإسلامية وضعف الكفاءات البشرية ونقص آليات الرقابة الشرعية. يخلص البحث إلى أن تطوير الحوكمة الشرعية في أفغانستان يتطلب إصلاحات جوهرية، تشمل تعديل قانون البنك المركزي، تعزيز صلاحيات واستقلالية المجلس الاستشاري الشرعي، وإعادة تأهيل الكوادر المصرفية. كما يشير البحث إلى أهمية اتباع نهج تدريجي لتحويل النظام المالي إلى نموذج إسلامي متكامل، مع الاستفادة من التجربة الماليزية في بناء إطار قانوني وتنظيمي يدعم التنمية الاقتصادية المستدامة. يؤكد البحث أن الحوكمة الشرعية ليست فقط آلية لضمان الامتثال الشرعي، بل هي أيضًا أداة استراتيجية لتحقيق الشفافية والمساءلة، ودعم النمو الاقتصادي والاستقرار المالي، مما يجعلها عاملاً محوريًا في بناء نظام مالي إسلامي قوي ومتوافق مع متطلبات العصر. ABSTRACT This research provides an in-depth analytical study of Sharia governance in the Islamic banking system, comparing the Afghan experience with Malaysia’s pioneering model. The study is based on a review of literature, analysis of relevant laws and regulations, and interviews with industry experts to explore how Sharia governance ensures compliance with Islamic principles and enhances financial stability. The findings highlight Malaysia’s superior framework, supported by a comprehensive legal system, the independence of Sharia boards, and the adoption of advanced operational standards, such as the Islamic Financial Services Act 2013 and the Sharia Governance Standard 2019. Conversely, the Afghan system faces challenges such as the absence of an independent Islamic banking law, a lack of qualified personnel, and insufficient Sharia compliance mechanisms. The research concludes that developing Sharia governance in Afghanistan requires fundamental reforms, including amending the Central Bank Law, strengthening the authority and independence of the Sharia Supervisory Council, and retraining banking personnel. The study also emphasizes the importance of adopting a gradual approach to transitioning the financial system into a fully Islamic model, leveraging Malaysia’s experience in establishing a legal and regulatory framework that supports sustainable economic development. It asserts that Sharia governance is not merely a tool for ensuring compliance but also a strategic mechanism for promoting transparency, accountability, and economic growth while fostering financial stability. As such, Sharia governance serves as a pivotal factor in building a robust Islamic financial system that aligns with contemporary demands.